Obowiązek alimentacyjny dziadków wobec wnuków. Analiza przypadku - Nowicka, Urszula (Ius Matrimoniale, 2016)
Nowadays, the issues of the alimony obligation is very timely. This applies not only to maintenance of parents of children, but also exists in other family relationships. The purpose of this article is present the issues of the alimony obligation between grandparents and grandchildren. This analysis is made on the basis of the case, chich happener by the District Court in Lublin. It will be shown the facts, the legal status of the case and the reasons for the decision.